Non-apoptotic FAS signaling controls mTOR activation and extrafollicular maturation in human B cells - Staniek, Julian; Kalina, Tomas; Andrieux, Geoffroy; Boerries, Melanie; Janowska, Iga; Fuentes, Manuel; Díez, Paula; Bakardjieva, Marina; Stancikova, Jitka; Raabe, Jan; Neumann, Julika; Schwenk, Sabine; et al. (Science immunology, 2024)
Defective FAS (CD95/Apo-1/TNFRSF6) signaling causes autoimmune lymphoproliferative syndrome (ALPS). Hypergammaglobulinemia is a common feature in ALPS with FAS mutations (ALPS-FAS), but paradoxically, fewer conventional memory cells differentiate from FAS-expressing germinal center (GC) B cells. Resistance to FAS-induced apoptosis does not explain this phenotype. We tested the hypothesis that defective non-apoptotic FAS signaling may contribute to impaired B cell differentiation in ALPS. We analyzed secondary lymphoid organs of patients with ALPS-FAS and found low numbers of memory B cells, fewer GC B cells, and an expanded extrafollicular (EF) B cell response. Enhanced mTOR activity has been shown to favor EF versus GC fate decision, and we found enhanced PI3K/mTOR and BCR signaling in ALPS-FAS splenic B cells. Modeling initial T-dependent B cell activation with CD40L in vitro, we showed that FAS competent cells with transient FAS ligation showed specifically decreased mTOR axis activation without apoptosis. Mechanistically, transient FAS engagement with involvement of caspase-8 induced nuclear exclusion of PTEN, leading to mTOR inhibition. In addition, FASL-dependent PTEN nuclear exclusion and mTOR modulation were defective in patients with ALPS-FAS. In the early phase of activation, FAS stimulation promoted expression of genes related to GC initiation at the expense of processes related to the EF response. Hence, our data suggest that non-apoptotic FAS signaling acts as molecular switch between EF versus GC fate decisions via regulation of the mTOR axis and transcription. The defect of this modulatory circuit may explain the observed hypergammaglobulinemia and low memory B cell numbers in ALPS.
Keywords: hypergamaglobulinemie; Hypergammaglobulinemia; Germinal Center; lymfoproliferativní nemoci; apoptóza; Humans; Lymphoproliferative Disorders; TOR Serine-Threonine Kinases; TOR serin-threoninkinasy; zárodečné centrum lymfatické uzliny; lidé; Apoptosis